Influence of ballistic bench press on upper body power output in professional rugby players - West, D. J.; Cunningham, D. J.; Crewther, B. T.; Cook, C. J.; Kilduff, L. P. (The Journal of Strength and Conditioning Research, 2013)
The use of heavy resistance exercise provides an effective preload stimulus for inducing postactivation potentiation (PAP) and increasing peak power output (PPO). However, this approach has limited application in many sporting situations (e.g., incorporation in a precompetition warm-up); and therefore, more practical strategies for inducing PAP need to be investigated. The aim of the present study was to compare the PPO changes after performing a preload stimulus of either a ballistic exercise or a traditional heavy resistance exercise. Twenty professional rugby union players completed 3 testing sessions, each separated by 48 hours. On the first occasion, subjects underwent a 3 repetition maximum (3RM)-bench press testing session. On the next 2 occasions, subjects performed a ballistic bench throw at baseline (30% of 1RM), followed by a preload stimulus of either heavy resistance training (HRT) (heavy bench press: 3 sets of 3 repetitions at 87% 1RM) or BBP (3 sets of 3 repetitions at 30% on 1RM) followed by ballistic bench throw after 8 minutes recovery. The trials were randomized and counterbalanced. Both preload stimuli protocols increased PPO compared with baseline (BBP baseline 892 ± 108 vs. 8 minutes 924 ± 119 W, p < 0.001; HRT baseline 893 ± 104 vs. 8 minutes 931 ± 116 W; p < 0.001). There were no conditional differences between PPO at 8 minutes (p = 0.141); moreover, the change in PPO from baseline was also similar between conditions (BBP ? + 33 ± 18; HRT d + 38 ± 21 W; p = 0.112). In conclusion, a ballistic exercise provided an effective method of inducing PAP and increasing upper-body PPO; moreover, this elicited similar increases in PPO as a traditional heavy resistance exercise preloading stimulus.